2007
DOI: 10.1016/j.proci.2006.07.186
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of a laboratory-scale turbulent slot flame

Abstract: We present three-dimensional, time-dependent simulations of the flowfield of a laboratory-scale slot burner. The simulations are performed using an adaptive time-dependent low Mach number combustion algorithm based on a second-order projection formulation that conserves both species mass and total enthalpy. The methodology incorporates detailed chemical kinetics and a mixture model for differential species diffusion. Methane chemistry and transport are modeled using the DRM-19 mechanism along with its associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(57 citation statements)
references
References 21 publications
(21 reference statements)
4
51
0
Order By: Relevance
“…The flame is similar to the flames studied by Filatyev et al [9], Bell et al [10], and Sankaran et al [11], with parameters somewhat altered in our case, to enable direct numerical simulation (DNS) with moderate computational effort. Both LES and DNS in the present paper assume flamelet chemistry, but unlike LES, the DNS resolves both flame thickness and turbulence down to the Kolmogorov length-scale.…”
Section: Introductionsupporting
confidence: 52%
“…The flame is similar to the flames studied by Filatyev et al [9], Bell et al [10], and Sankaran et al [11], with parameters somewhat altered in our case, to enable direct numerical simulation (DNS) with moderate computational effort. Both LES and DNS in the present paper assume flamelet chemistry, but unlike LES, the DNS resolves both flame thickness and turbulence down to the Kolmogorov length-scale.…”
Section: Introductionsupporting
confidence: 52%
“…Bell et al [5] produced the first simulation of a turbulent methane flame in three dimensions with moderate-fidelity kinetics using DRM-19, which 20 is a simplified mechanism derived from GRIMech 1.2. Simulations using DRM-19 for a variety of experimental configuration have been presented in [6,7]. Sankaran et al [8] performed a DNS of the lean premixed preheated methane flame stabilised on a slot burner using a skeletal mechanism with 13 species derived from GRIMech 1.2.…”
mentioning
confidence: 99%
“…This software is the product of the mathematical and computational research reported in [27,[30][31][32] and references therein. Calculations made with this methodology compare well with turbulent flame experiments [33,34] The calculations reported here consider a hydrogen-air mixture with equivalence ratio φ=0.2 (volume of fuel 7.75%) which does not appear to support a planar flame at standard temperatures and pressures. The percentage of fuel is above the listed [35] flammability limit (4%) but between the values (4% and 9%) reported (e. g. [15], p.10) for upwardly and downwardly propagating, non-planar flames.…”
Section: Direct Numerical Simulationmentioning
confidence: 68%